Self-Adjustment Profile of Guidance and Counseling Study Program Students, PGRI University, West Sumatra - Yunan, Fadilla Faizal; Mulyani, Rahma Rila; Putri, Besti Nora Dwi (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2024)
This research is motivated by the existence of students who experience problems in adjusting themselves so that they experience obstacles and barriers and enter a new environment and situation. This study aims to see: 1). Student adjustment seen from the Knowledge and Self Insight Aspects, 2). Student adjustment seen from Self Objectifity and Self Acceptance, 3). Student adjustment seen from Self Development and Self Control and 4). Student adjustment seen from the Statisfaction Aspect. Profile of Guidance and Counseling Student Adjustment in 2023, Guidance and Counseling Study Program, West Sumatra PGRI University. This type of research is quantitative descriptive. With a population of guidance and counseling students in 2023 of 90 respondents. The sampling technique used is the random sampling technique where the sample is taken randomly with half of the specified population. So that the sample in this study amounted to 45 people. Using a questionnaire as a data collection tool using descriptive statistical analysis techniques in analyzing data. Based on the results of the research and data analysis that have been carried out, it was revealed that: 1). The adjustment of guidance and counseling students in 2023 is generally in the good criteria (56%). 2) Self-Knowledge and self-insight indicators have good criteria (51%), Self-Objectivity and Self-Acceptance indicators are in the good criteria (56%), Self-Development and Self-Control indicators are in the good criteria (53%) and Statisfaction is in the good criteria (40%). These results are recommended for Guidance and Counseling Students as input in making adjustments to the new environment in the future and becoming better for all the shortcomings that have been made.